Virtual Reality in Science Education: a Descriptive Review - Alper Durukan; Huseyin Artun; Atilla Temur (Journal of Science Learning, 2020)
The term “Virtual Reality” currently refers to a profound sensory immersion of the user in a synthetically generated virtual environment. It is foreseen that virtual reality will gain a substantial role in the instruction of science. In this literature review, the purpose was to investigate the research on the utilization of virtual reality in the science education context, according to several criteria. The articles published in peer-reviewed journals and academic conferences/symposiums that are available in the databases of ERIC, WOS, and Google Scholar have been reviewed. Consequently, a total of 30 eligible articles reviewed and findings presented under every respective criterion. Partially, findings revealed the dominance of journal article type publications, the USA and Turkey found to be most prominent origins, experimental studies being preferred mostly, undergraduate students and pre-service teachers were the most studied groups, the contexts of the studies were prominently general, and the learning outcomes investigated mostly.